A Time Slot Reservation in Modified TDMA-Based Ad Hoc Networks with Directional Antennas - Yuan Li; Baolin Sun; Xing Luo; Naixue Xiong (International Journal of Distributed Sensor Networks)
In this paper, we study the bandwidth reservation issue in wireless ad hoc networks with directional antennas. Providing Quality of Service (QoS) support in the wireless ad hoc networks is one of the topics that have received a lot of attention in recent years. QoS provisioning is needed to support multimedia and real-time application in wireless networks. In the Time Division Multiple Accesses (TDMA) frame, the bandwidth is measured by the number of the data time slots. Control slots in the traditional TDMA frame can be used for transmission of the control packets, rather than the transmission of the data packets. We focus on the problem of how to make full use of slots to transmit data packets and do not affect control packets transmission. The purpose is to improve the time slot utilization rate. Based on our proposed modified TDMA frame, a novel time slot reservation algorithm is presented to achieve maximal available path bandwidth. Directional antennas allow transmission energy to be concentrated on a narrow range along a particular direction, which can significantly increase the data rate. The performance of our scheme is analyzed and implemented. Simulation results show that the proposed scheme performs better.